Proteomic Profiling of the Dystrophin-Deficient MDX Heart Reveals Drastically Altered Levels of Key Metabolic and Contractile Proteins. (23rd May 2010) - Lewis, Caroline; Jockusch, Harald; Ohlendieck, Kay
Abstract : Although Duchenne muscular dystrophy is primarily classified as a neuromuscular disease, cardiac complications play an important role in the course of this X-linked inherited disorder. The pathobiochemical steps causing a progressive decline in the dystrophic heart are not well understood. We therefore carried out a fluorescence difference in-gel electrophoretic analysis of 9-month-old dystrophin-deficient versus age-matched normal heart, using the established MDX mouse model of muscular dystrophy-related cardiomyopathy. Out of 2, 509 detectable protein spots, 79 2D-spots showed a drastic differential expression pattern, with the concentration of 3 proteins being increased, including nucleoside diphosphate kinase and lamin-A/C, and of 26 protein species being decreased, including ATP synthase, fatty acid binding-protein, isocitrate dehydrogenase, NADH dehydrogenase, porin, peroxiredoxin, adenylate kinase, tropomyosin, actin, and myosin light chains. Hence, the lack of cardiac dystrophin appears to trigger a generally perturbed protein expression pattern in the MDX heart, affecting especially energy metabolism and contractile proteins.